A study on the frictional changes of steel bracket on the stainless steel wire during sliding - Shiva Alavi; Zohreh Tabatabaei (Isfahan University of Medical Sciences, 2010)
Introduction: Though sliding techniques are quite common in orthodontics, the produced friction however hampers ideal movement of teeth. Increased friction not only necessitates a greater orthodontic force but also results in anchorage loss. The aim of this study was to evaluate frictional changes of steel brackets on stainless steel wires while sliding. Materials and Methods: In this experimental study a total of 69 stainless steel brackets (Dentaurum) with 0.018 inch slots were randomly divided into three groups of 23 brackets. With each group either 0.016 or 0.016 × 0.016 or 0.016 × 0.022 inch steel wires of the same company (Dentaurum) were used in combination with brackets. There were 5 slots on each piece and every slot was 1mm apart from the next. Therefore each piece of wire was pulled via Dartec machine in every bracket slot with an average speed of 0.5mm/min in five sections. The amounts of friction were recorded. The collected data were then compared with repeated measurement ANOVA and paired sample T-test.(α = 0.05) Three brackets were randomly examined under scanning electron microscope (SEM) at the beginning and after the first, the third and the fifth tractions.Results: Repeated measurement ANOVA showed statistical significant differences in static and kinetic frictions between first to fifth tractions in three sizes of wires. Based on paired sample t-test, significant differences were seen between first traction and the others. However, differences between the third and the forth, the third and the fifth and the forth and the fifth tractions were not significant between the three sizes of wires and the two kinds of frictions.Conclusion: It seems that friction would decrease during sliding of steel brackets on steel wires. Diameter and cross section of wires would have little effect on friction. Key words: Frictional changes, Sliding, Static friction, Kinetic friction.